2022
DOI: 10.2147/jmdh.s392848
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Smoking on Renal Functions Among Apparently Healthy Smokers

Abstract: Background Cigarette smoking is an important modifiable risk factor in kidney disease progression. Although long-term smoking has been associated with chronic kidney disease (CKD), its effect on kidney function in early stages has not been clarified. Objective To detect the early effects of smoking either active or passive on kidney functions. Methodology The current study was comparative cross sectional study conducted on 280 participants, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Our study significantly difference in elevation in RDW, Urea, creatinine, RBS, FBS, PPBS, and HbA1C levels among patients with both smoking and alcohol consumption habits. A similar study conducted by Eid HA et al in 2022 concluded that increase in urea and creatinine levels, accompanied by a decline in eGFR values among patients with smoking and alcohol consumption habits [14]. Smoking can potentially inflict damage on the kidneys through diverse mechanisms, encompassing immediate effects such as sympathetic stimulation leading to reduced GFR, as well as on-going consequences, notably compromised endothelial cell functionality [15].…”
Section: Dm First Report Dm Latest Report Diabetic Nephropathymentioning
confidence: 91%
“…Our study significantly difference in elevation in RDW, Urea, creatinine, RBS, FBS, PPBS, and HbA1C levels among patients with both smoking and alcohol consumption habits. A similar study conducted by Eid HA et al in 2022 concluded that increase in urea and creatinine levels, accompanied by a decline in eGFR values among patients with smoking and alcohol consumption habits [14]. Smoking can potentially inflict damage on the kidneys through diverse mechanisms, encompassing immediate effects such as sympathetic stimulation leading to reduced GFR, as well as on-going consequences, notably compromised endothelial cell functionality [15].…”
Section: Dm First Report Dm Latest Report Diabetic Nephropathymentioning
confidence: 91%
“…Additionally, a previous study showed that among smokers, higher serum concentrations of cotinine were significantly associated with serum creatinine compared with non-smokers 17 . Our results are similar to those of a previous study, which showed higher levels of creatinine-based eGFR and lower levels of cystatin C-based eGFR with higher quantities of smoking 11 .…”
Section: Correlation Between Urinary Cotinine Metabolite and Serum Eg...mentioning
confidence: 93%
“…The definition of an active cigarette smoker in this study was calculated using the smoking index (SI) as the number of packs smoked daily multiplied by the number of years of smoking. The SI was used to categorize active smokers as: 1) mild active cigarette smokers (SI<400 cigarettes/year), 2) moderate active cigarette smokers (SI = 400-800 cigarettes/year), and 3) heavy active cigarette smokers (SI ≥800 cigarettes/ year) 17,23 . The National Center for Health Statistics 2017 defined a current smoker as a person who has smoked ≥100 cigarettes in their lifetime and who is still smoking cigarettes 17 .…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eid HA et al. [ 15 ] found that serum cotinine was significantly positive with tobacco exposure, the research had reinforced a conclusion that there was a negative correlation between serum cotinine and the eGFR. However, the association between serum hydroxycotinine, transformed by continine, and CKD is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 96%